CONSUMER PERCEPTIONS OF USER EXPERIENCE AND RISK: A RESEARCH ON ONLINE SHOPPING - (:unkn) unknown (FUTURE ACAD, 2019)
Providing consumers with a web site that leads consumers to perceive less risk, have a satisfying experience, and trigger consumers to purchase online are crucial for e-retailers. Online consumer reviews can be affected by risk perceptions toward a product or e-retailer. Moreover designing a friendly web site can lead consumers to purchase online. In this vein, this study aims to examine the effect of consumer reviews on perceived risk and the mediating role of user experience on the relationship between perceived risk and online purchase intention. 345 fully answered online surveys were collected from participants who purchased single-purchase items via online channels and structural equation modelling was performed for analyses. The findings state that consumer reviews do not have effect on financial risk; however, it is found that consumer reviews reduce perceived convenience risk and increase product risk, and convenience risk affects the tendency for shopping online. Finally, user experience positively mediates the relationship between convenience risk and online purchase intention. (C) 2019 Published by Future Academy www.FutureAcademy.org.uk
Keywords: Online consumer reviews; online purchase intention; perceived risk; user experience; WORD-OF-MOUTH; PERCEIVED RISK; PURCHASE INTENTION; REPURCHASE INTENTIONS; ELECTRONIC COMMERCE; MODERATING ROLE; TRUST; DETERMINANTS; IMPACT; TECHNOLOGY